2006
DOI: 10.1901/jaba.2006.24-05
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Stimulant Medication on Response Allocation: A Double‐blind Analysis

Abstract: Children who are diagnosed with attention deficit hyperactivity disorder (or who engage in behavior consistent with such a diagnosis) are often prescribed stimulant medications for hyperactive or inattentive behaviors. However, the mechanisms by which stimulant medications affect individuals' behavior are rarely evaluated. The purpose of the current study was to evaluate the effects of stimulant medication on response allocation when antecedents and consequences were held constant and equated. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A double-blind procedure is one in which neither the subjects nor the persons who conduct the experiment are informed about its critical aspects; a double-blind procedure guards against both experimenter bias and placebo effects. For example, Kelley et al (2006) assessed the effects of the stimulant Adderall on response allocation when antecedents and consequences were held constant and equated in a child with mild mental retardation and ADHD. In their study, only the school nurse was aware of whether placebo or medication had been administered on any given day.…”
Section: Use Double-blind Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind procedure is one in which neither the subjects nor the persons who conduct the experiment are informed about its critical aspects; a double-blind procedure guards against both experimenter bias and placebo effects. For example, Kelley et al (2006) assessed the effects of the stimulant Adderall on response allocation when antecedents and consequences were held constant and equated in a child with mild mental retardation and ADHD. In their study, only the school nurse was aware of whether placebo or medication had been administered on any given day.…”
Section: Use Double-blind Proceduresmentioning
confidence: 99%
“…The Journal of Applied Behavior Analysis (JABA) has published a considerable number of articles on the effects of pharmacological agents on socially relevant behaviors. Most of these studies involved the examination of the effects of psychomotor stimulant drugs on the behavior of individuals who had been diagnosed with some form of attention deficit hyperactivity disorder (ADHD; Ardoin & Martens, 2000;Ayllon, Layman, & Kandel, 1975;Blum, Mauk, McComas, & Mace, 1996;Burgio, Page, & Capriotti, 1985;Dicesare, McAdam, Toner, & Varrell, 2005;Gulley & Northup, 1997;Gulley et al, 2003;Kayser et al, 1997;Kelley, Fisher, Lomas, & Sanders, 2006;LaRue et al, 2008;Mace et al, 2009;Murray & Kollins, 2000;Neef, Bicard, Endo, Coury, & Aman, 2005;Northup et al, 1999;Northup, Fusilier, Swanson, Roane, & Borrero, 1997;Northup, Jones, et al, 1997;Pelham, Schnedler, Bologna, & Contreras, 1980;Rapport, Murphy, & Bailey, 1982;Shafto & Sulzbacher, 1977;Stoner, Carey, Ikeda, & Shinn, 1994;Whalen, Henker, Collins, Finck, & Dotemoto, 1979;Wulbert & Dries, 1977). A few studies concerned the behavioral effects of other pharmacological agents such as thioridazine (Burgio et al, 1985), chlorpromazine (Marholin, Touchette, & Stewart, 1979), risperidone (Yoo et al, 2003), and sertraline (Miguel, Clark, Tereshko, & Ahearn, 2009).…”
mentioning
confidence: 99%
“…Although PR schedules are commonly used in psychopharmacological research to evaluate the reinforcing efficacy of different drugs or dosages (see Stafford, LeSage, & Glowa, 1998, for a review), such procedures have yet to be applied to the study the therapeutic effects of pharmacological interventions in applied settings. A number of recent contributions to JABA by Northup and colleagues (Gulley & Northup, 1997;Northup et al, 1999;Northup, Fusilier, Swanson, Roane, & Borrero, 1997;Northup, Jones, et al, 1997) and others (Kelley, Fisher, Lomas, & Sanders, 2006;Yoo et al, 2003) have focused on the use of medications to treat destructive behavior problems. The use of PR schedules could augment such research.…”
Section: Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…Clinical improvements have been reported for behaviors directly related to enhanced attention, such as task engagement and work completion. Collateral benefits have also been observed, such as reduced disruptive behavior, physical aggression, and noncompliance that may, in part, be due to increased academic activity and compliance (e.g., Kelley, Fisher, Lomas, & Sanders, 2006).…”
mentioning
confidence: 99%
“…In addition to demonstrating favorable clinical outcomes, several studies have demonstrated that stimulant medication can alter an individual's response to specific environmental conditions. For example, Blum et al (1996), Kayser et al (1997), Kelley et al (2006), Northup, Fusilier, Swanson, Roane, and Borrero (1997), and Northup et al (1999) demonstrated improved response to common behavioral interventions such as token systems, differential reinforcement of alternative behavior, time-out, and reprimands with stimulant medication compared to placebo, and Northup, Jones, et al (1997) and Dicesare, McAdam, Toner, and Varrell (2005) found that participants were more sensitive to some functional analysis conditions without stimulant medication than with it. These findings support consideration of the use of stimulant medication in conjunction with established behavioral interventions, especially be-cause assessment of a clinical response to the medication can be readily established in many cases (Kayser et al; Kelley et al).…”
mentioning
confidence: 99%